Scientific and ethical features of English‐language online tests for Alzheimer's disease. Issue 3 (2nd July 2015) - Robillard, Julie M.; Illes, Judy; Arcand, Marcel; Beattie, B. Lynn; Hayden, Sherri; Lawrence, Peter; McGrenere, Joanna; Reiner, Peter B.; Wittenberg, Dana; Jacova, Claudia
Abstract: Introduction: Freely accessible online tests for the diagnosis of Alzheimer's disease (AD) are widely available. The objective of this study was to evaluate these tests along three dimensions as follows: (1) scientific validity; (2) human‐computer interaction (HCI) features; and (3) ethics features. Methods: A sample of 16 online tests was identified through a keyword search. A rating grid for the tests was developed, and all tests were evaluated by two expert panels. Results: Expert analysis revealed that (1) the validity of freely accessible online tests for AD is insufficient to provide useful diagnostic information; (2) HCI features of the tests are adequate for target users, and (3) the tests do not adhere to accepted ethical norms for medical interventions. Discussion: The most urgent concerns raised center on the ethics of collecting and evaluating responses from users. Physicians and other professionals will benefit from a heightened awareness of these tools and their limitations today.